Abolishing the Death Penalty: An Untested Legal Argument - Sarver, Vernon Thomas (American journal of criminal justice, 2014)
This paper supplies the logical and substantive framework for an untested challenge to the legality of the death penalty in the United States. As such, it yields a novel strategy for appellants and supporting amici seeking review of capital cases in the United States Supreme Court. With twin reliance on the right of the people to reparation for harm wrongly inflicted by others and their constitutional right to Due Process of Law under the Fourteenth Amendment, this paper advances the argument that the mere possibility of a wrongful execution yields an imperative for abolishment of capital punishment by the Court.